"And I Am Also Gay": Illiberal Pragmatics, Neoliberal Homonormativity and LGBT Activism in Singapore - Phillips, Robert (Anthropologica, 2014)
For decades, members of Singapore’s LGBT com munities have been unsuccessfully advocating for rights. How ever, since the state introduction of the Internet, there has been a profound shift in the relationship between LGBT Singa poreans and their nation. In this article I examine recent Internet-influenced developments in LGBT activism and posi tion them within the framework of illiberal pragmatics, which highlights the ambivalent logic employed by Singaporean au thorities when formulating social and legal policy. I describe how illiberal pragmatism, in combination with a Singaporean specific neoliberal homonormativity, has changed strategies of LGBT activism and provided new ways to think about rights.